Analysis on pathogenic and virulent characteristics of the Cronobacter sakazakii strain BAA-894 by whole genome sequencing and its demonstration in basic biology science. (August 2017) - Bao, Xuerui; Yang, Ling; Chen, Lequn; Li, Bing; Li, Lin; Li, Yanyan; Xu, Zhenbo
Abstract: Cronobacter sakazakii is an opportunistic pathogen responsible for necrotizing enterocolitis, meningitis and septicaemia especially to infant and neonate, with high lethality ranging in 40%–80%. This strain is able to survive in infant milk formula and possesses capability of pathogenicity and virulence, biofilm formation, and high resistance to elevated osmotic, low pH, heat, oxidation, and desiccasion. This study is aims to investigate the molecular characteristics of Cronobacter sakazakii BAA 894, including mechanisms of its invasion and adherence, biofilm formation, unusual resistance to environmental stress employing whole genome sequencing and comparative genomics. Results in this study suggest that numerous genes and pathways, such as LysM, Cyx system, luxS, vancomycin resistance pathway, insulin resistance pathway, and sod encoding superoxide dismutase for the survival of C. sakazakii in macrophages, contribute to pathogenicity and resistance to stressful environment of C. sakazakii BAA 894. Highlights: Finally assembly yielded to 135 scaffolds, total length of 4, 435, 442 bp with G + C content of 56.53%. Pathways of vancomycin resistance and insulin resistance were identified. Outer membrane protease encoded by cpa gene was identified in this strain.